2017
DOI: 10.1016/j.jamda.2017.05.025
|View full text |Cite
|
Sign up to set email alerts
|

What Works to Improve and Manage Fecal Incontinence in Care Home Residents Living With Dementia? A Realist Synthesis of the Evidence

Abstract: The prevalence of fecal incontinence (FI) in care homes is estimated to range from 30% to 50%. There is limited evidence of what is effective in the reduction and management of FI in care homes. Using realist synthesis, 6 potential program theories of what should work were identified. These addressed clinician-led support, assessment, and review; the contribution of teaching and support for care home staff on how to reduce and manage FI; addressing the causes and prevention of constipation; how cognitive and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 98 publications
1
34
0
1
Order By: Relevance
“…After title and abstract screening, and removal of duplicates, 55 articles were reviewed at full-text level. From these, 18 articles [21,23,30,32,33,[68][69][70][71][72][73][74][75][76][77][78][79][80] (see Fig. 1 for the PRISMA flow chart) were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After title and abstract screening, and removal of duplicates, 55 articles were reviewed at full-text level. From these, 18 articles [21,23,30,32,33,[68][69][70][71][72][73][74][75][76][77][78][79][80] (see Fig. 1 for the PRISMA flow chart) were included.…”
Section: Resultsmentioning
confidence: 99%
“…Among the eligible articles were three studies that were reported in two or more papers. Specifically, the 'FINCH' study was reported in three papers [69,70,77]. Similarly, Ostaszkiewicz reported on different aspects of the same Grounded theory study about providing continence care in Australian residential aged care homes (RACH) in three papers [32,72,73].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews on the prevalence of fecal incontinence (FI) have concentrated on community dwellers. 1,2 To facilitate planning and provision of quality continence care in care homes 3 (a collective term for nursing or residential care settings, or aged care, or skilled nursing facilities), there is a need to understand the prevalence, incidence, and correlates of FI within care homes.…”
mentioning
confidence: 99%
“…15 An estimated 50% of older people living in care homes experience FI, compared with 18% of the general population. 19,22 FI may result in low self-esteem, stigmatization, 3 and feeling of social isolation, 23 and in some cases it predicts mortality. 24,25 Generally, people are embarrassed to discuss their experience of FI with health care professionals or even with friends and family, as it can be seen as a "taboo within stigma" 26 ; this is also the case in care homes.…”
mentioning
confidence: 99%